Qualitative and quantitative determination of chemical constituents in Jinbei oral liquid, a modern Chinese medicine for coronavirus disease 2019, by ultra-performance liquid chromatography coupled with mass spectrometry - Zhang, Aijun; Xu, Qingcui; Jiang, Juanjuan; Zhao, Zimo; Zhang, Liangzong; Tao, Kai; Cao, Guiyun; Zhang, Jinghua; Ding, Lin; Meng, Zhaoqing; Dong, Wenyao; Wang, Chunxia (Frontiers in Chemistry, 2023)
Introduction: Traditional Chinese medicine (TCM) has the advantages of syndrome differentiation and rapid determination of etiology, and many TCM prescriptions have been applied to the clinical treatment of coronavirus disease 2019 (COVID-19). Among them, Jinbei Oral Liquid (Jb.L) has also shown an obvious curative effect in the clinic, but the related material basic research is relatively limited. Methods: Therefore, in this process, a systematic data acquisition and mining strategy was established using ultra-high- performance liquid chromatography coupled with quadruple time-of-flight mass spectrometry (UPLC-Q-TOF-MS). Results and Discussion: With the optimized conditions, a total of 118 peaks were tentatively characterized, including 43 flavonoids, 26 phenylpropanoids, 14 glycosides, 9 phthalides, 8 alkaloids and others. To determine the content of relevant pharmacological ingredients, we firstly exploited the ultra-performance liquid chromatography method coupled with triple-quadrupole tandem mass spectrometry (UPLC-QqQ-MS/MS) method for simultaneous detection of 31 active ingredients within 17 min, and the validation of methodology showed that this method has good precision and accuracy. Moreover, analyzing the pharmacology of 31 individual of the medicinal material preliminarily confirmed the efficacy of Jb.L and laid a foundation for an in-depth study of network pharmacology.